CFD simulations to study the effects of wall protrusions on microfluidic mixing. (22nd July 2015) - Sarkar, Sourav; Singh, K K; Shankar, V; Shenoy, K T
Abstract: In this study the effects of different types of wall protrusions on microfluidic mixing are studied using computational fluid dynamics (CFD) simulations. Two new protrusions, single first bracket protrusions and double opposite first bracket protrusions (DOFBPs), are conceptualized, evaluated through CFD simulations and compared to protrusions having standard geometrical shapes, e.g. rectangular protrusions, triangular protrusions and semicircular protrusions. In the range of Reynolds numbers covered in this study, the microchannel having an opposed T-junction and DOFBPs is found to provide good mixing. A hybrid approach relying on the modification of microfluidic junctions as well as wall protrusions for enhancing microfluidic mixing is also evaluated. The microchannel based on the hybrid approach of an OA 10°–20°–165° WY-junction and DOFBPs is also found to provide very good mixing for a wide range of Reynolds numbers.